The Influence of Price Discounts, Perceptions of Price, and Product Quality on Online Purchase Decisions Baba Rafi Turkish Kebab Surabaya - Meylani Yulia Putri; Sugeng Purwanto (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
Development business culinary increasingly day develop faster, indeed innovations carried out by actors business culinary make competition become the tighter, of course, matter This requires the perpetrators business culinary For Determine effective strategies so that you can survive and compete in the market. Baba Rafi is one of them business culinary with product main they namely Kebab Turki Baba Rafi. Several months Lastly, Baba Rafi experienced a decline in sales online, so the company need apply draft strategic marketing To raise sales. Study This done aims to know how much the existing level influences Price Discounts, Price, and Quality Perceptions of products on online purchasing decisions for Kebab Turki Baba Rafi. Method quantitative used in researching this and its population is Baba Rafi's existing customers do Purchase Turkish Kebab Baba Rafi online via food delivery order with a minimum of one transaction. Samples were taken totaling 50 respondents who have filled in the questionnaire via Google Form. Data obtained was processed with using IBM SPSS Version 22 software and analysed with used method analysis multiple linear regression. Findings from the study state that price Discounts individually are not influenced by decision purchases, however together with Price and Quality Perceptions Products have a significant impact and are influential to existing decision purchases